Multi-layer composite film for battery cell and preparation method of multi-layer composite film

By using specific composite glue formula and surface treatment technology in the multi-layer composite film of the battery cell, the problem of degradation of aluminum-plastic film in high humidity and heat environment is solved, and the composite film is excellent in heat resistance in high temperature and high humidity environments is achieved. Performance ensures the safety and performance of the battery cell.

CN119427856AActive Publication Date: 2025-02-14浙江海顺新材料有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411498345.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Aluminum-plastic films are prone to problems such as nylon layer water absorption, composite glue hydrolysis reaction, aluminum foil oxidation in high humidity and heat environments, resulting in a decline in its performance and may cause leakage of electrolyte inside the power core, affecting the electrochemical performance and service life.

Method used

A multi-layer composite film consisting of a nylon layer, an aluminum foil layer and a polypropylene cast film layer is used, and its heat resistance is improved through specific composite glue formulations and surface treatment techniques. Compound glue includes aromatic polyester polyols, oligomeric polyols, epoxy resins, tributyl citrates and nanocellulose, and forms a glue system with high mechanical strength and heat resistance through cross-linking reaction.

Benefits of technology

In high temperature and high humidity environments, the composite film can maintain excellent performance, prevent the leakage of electrolyte inside the battery cell, prolong the service life of the battery cell, and improve user safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101870900000071
    Figure BDA0005101870900000071
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum plastic films, and relates to a multi-layer composite film for a battery cell and a preparation method of the multi-layer composite film. Aromatic polyester polyol (polycarbonate diol) and oligomer polyol (such as butadiene diol, polybutadiene-acrylonitrile copolymerized diol and castor oil) are combined to form a glue system with good mechanical property and good flexibility, so that the overall performance of the composite film is improved; the polycarbonate diol and the epoxy resin form a three-dimensional network structure through a cross-linking reaction, so that the mechanical strength and the heat resistance of the glue are remarkably improved, and the stability and the durability of the composite film are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum-plastic films and relates to a multilayer composite film for an electric core and a preparation method thereof. Background Art

[0002] Aluminum-plastic film is exposed to high humidity (≥70% RH) and high temperature (≥30°C) before transportation and processing of battery cells, and after filling the battery cells. Such high humidity and heat conditions bring great challenges and risks to the performance and structure of aluminum-plastic film. Aluminum-plastic film is usually composed of multiple layers of composite materials, including nylon layer, aluminum foil layer and polypropylene cast film layer, and the layers are bonded by composite glue. Each layer of material has its specific response mechanism in a high humidity and heat environment, but the most critical problem focuses on the interaction between the nylon layer and the aluminum foil layer.

[0003] First, the nylon layer has a certain degree of water absorption and is easy to absorb water in a high humidity environment, causing changes in its physical properties. The water absorption of nylon comes from the polar groups in its molecular chain, such as amide groups, which can form hydrogen bonds with water molecules, thereby attracting and fixing water molecules. As the water molecules gradually gather, the distance between the molecular chains of the nylon layer increases, resulting in a decrease in its strength and toughness. This change not only affects the mechanical properties of the nylon layer itself, but also has an adverse effect on its combination with other layers.

[0004] Secondly, the aggregation of water molecules will penetrate into the bonding layer between nylon and aluminum foil, destroying the bonding force between the two layers of materials. The composite glue may undergo hydrolysis reaction in a high humidity and heat environment, resulting in a decrease in its bonding performance. Once the bonding layer is damaged, the overall performance of the aluminum-plastic film will be significantly reduced, which may lead to problems such as weakened sealing and reduced barrier properties. These problems will not only affect the packaging effect of the battery cell, but may also cause leakage of the electrolyte inside the battery cell, thereby affecting the electrochemical performance and service life of the battery cell. The leakage of the electrolyte will cause a short circuit inside the battery, and in severe cases may even cause a fire or explosion, posing a threat to user safety.

[0005] In addition, high humidity and heat environment may also accelerate the oxidation process of aluminum foil, further weakening the protective ability of aluminum plastic film. Aluminum foil easily reacts with oxygen in a humid environment to form an aluminum oxide layer. Although the aluminum oxide layer itself has a certain protective effect, under high humidity and heat conditions, the aluminum oxide layer may become loose and lose its protective properties, thereby further exposing the aluminum foil to the corrosive environment. This will not only reduce the mechanical strength of the aluminum foil, but also increase its conductivity, affecting the normal operation of the battery cell. Summary of the invention

[0006] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a multilayer composite film for battery cells with excellent heat resistance, which can continue to maintain excellent performance in a high temperature and high humidity environment and will not cause performance degradation due to environmental changes.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A multilayer composite film for a battery cell, the multilayer composite film comprising, from top to bottom, a nylon layer, an aluminum foil layer and a polypropylene cast film layer, the nylon layer, the aluminum foil layer and the polypropylene cast film layer being bonded with a composite glue, wherein the composite glue comprises the following raw materials in parts by mass: 70-85 parts of aromatic polyester polyol, 5-7 parts of oligomer polyol, 1-5 parts of epoxy resin, 5-15 parts of tributyl citrate and 5-10 parts of nanocellulose.

[0009] In the above-mentioned multi-layer composite film for battery cells, the aromatic polyester polyol is polycarbonate diol.

[0010] In the above-mentioned multi-layer composite film for battery cells, the oligomer polyol includes at least one of butadiene glycol, polybutadiene-acrylonitrile copolymer glycol, and castor oil.

[0011] The present invention utilizes the combination of aromatic polyester polyol (polycarbonate diol) and oligomer polyol to form a glue system with both good mechanical properties and good flexibility, thereby improving the overall performance of the composite film. Polycarbonate diol and epoxy resin form a three-dimensional network structure through a cross-linking reaction, which significantly improves the mechanical strength and heat resistance of the glue, and enhances the stability and durability of the composite film. The combination of oligomer polyol and epoxy resin can form a tough and flexible glue system, further improving the mechanical properties and weather resistance of the glue. Tributyl citrate combined with nanocellulose can improve the flexibility and mechanical strength of the glue, while improving the dispersibility of nanocellulose and ensuring its uniform distribution in the glue. Epoxy resin and nanocellulose form a denser cross-linking structure through a cross-linking reaction, significantly improving the mechanical strength and heat resistance of the glue, while enhancing its barrier properties and preventing the penetration of water molecules and other harmful substances. The synergistic effect of oligomer polyol and tributyl citrate can improve the flexibility and fluidity of the glue, while improving its water resistance and preventing the penetration of water molecules. Finally, the composite glue of the present invention can not only effectively bond the materials of each layer of the multi-layer composite film, but also maintain good performance in a high humidity and heat environment, thereby ensuring the safety and performance of the battery core.

[0012] In the above-mentioned multi-layer composite film for battery cells, the surface of the nylon layer is coated with PE wax. Coating the surface of the nylon layer with PE wax can significantly improve its surface smoothness, reduce friction and wear, and improve production efficiency; at the same time, PE wax coating can effectively prevent the nylon layer from sticking during winding or stacking, ensuring smooth stratification of the composite film. In addition, the protective film formed by PE wax can reduce scratches and damage on the surface of the nylon layer, maintaining its integrity and aesthetics.

[0013] In the above-mentioned multilayer composite film for battery core, the concentration of PE wax coating is 1-3wt%, and the amount of dry glue coating is 0.1-0.5. The present invention can optimize the interface performance between the nylon layer and the composite glue by adjusting the coating amount and concentration of PE wax, enhance the bonding strength between the layers of the composite film, and ensure the stability and reliability of the overall performance.

[0014] In the above-mentioned multi-layer composite film for battery cells, the surface of the aluminum foil layer is coated with a passivation liquid, and the passivation liquid includes the following raw materials in parts by weight: 20-30 parts of acrylic resin, 5-10 parts of chromium-containing compounds, 0.5-2 parts of silane coupling agents, 1-3 parts of phosphates, 0.1-0.5 parts of sodium polyacrylate, and 60-70 parts of deionized water. The present invention can significantly improve its anti-oxidation and anti-corrosion properties by coating the surface of the aluminum foil layer with a passivation liquid, and by forming a dense protective film, the aluminum foil is prevented from oxidation and corrosion in a high humidity and heat environment, thereby extending its service life. The acrylic resin and silane coupling agent in the passivation liquid can enhance the bonding strength between the aluminum foil and the composite glue, and improve the overall stability and durability of the composite film. At the same time, sodium polyacrylate is used as a dispersant to ensure that the various components are evenly distributed on the surface of the aluminum foil, forming a smooth coating and improving the surface properties. In addition, the phosphate and chromium-containing compounds in the passivation solution can effectively block the penetration of water molecules and other harmful substances, improve the barrier properties of the aluminum foil, protect the battery from the influence of the external environment, and ensure its electrochemical performance and service life. In general, the aluminum foil layer coated with the passivation solution plays multiple positive roles in the preparation process of the multi-layer composite film, improving the overall performance and reliability of the composite film.

[0015] Preferably, the chromium-containing compound is chromic acid, which has strong oxidizing properties and can react with the surface of the aluminum foil to form a dense chromate protective film.

[0016] Preferably, the phosphate is zinc phosphate.

[0017] Preferably, the silane coupling agent is vinyltrimethoxysilane.

[0018] The present invention also provides a method for preparing the multilayer composite film for a battery cell, the method comprising the following steps:

[0019] S1. Apply a passivation solution on the surface of the aluminum foil, and then use a composite glue to composite the nylon layer, the aluminum foil layer and the polypropylene cast film layer;

[0020] S2, then carry out aging treatment;

[0021] S3. After aging and cooling, the surface of the nylon layer is coated with PE wax, and the surface of the polypropylene cast film layer is coated with lubricating powder, and finally the molding and curing are performed.

[0022] In the above-mentioned method for preparing a multi-layer composite film for a battery cell, the aging treatment temperature in step S2 is 70-85° C. and the time is 3-5 days.

[0023] In the above-mentioned method for preparing a multi-layer composite film for a battery core, the temperature for molding and curing is 30-40° C., and the relative humidity is 65-75%.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention forms a glue system having both good mechanical properties and good flexibility by combining aromatic polyester polyols (polycarbonate diol) with oligomer polyols (such as butadiene diol, polybutadiene-acrylonitrile copolymer glycol, castor oil), thereby improving the overall performance of the composite film. The polycarbonate diol and the epoxy resin form a three-dimensional network structure through a cross-linking reaction, which significantly improves the mechanical strength and heat resistance of the glue, and enhances the stability and durability of the composite film.

[0026] 2. The present invention utilizes tributyl citrate in combination with nanocellulose to improve the flexibility and mechanical strength of the glue, while improving the dispersibility of nanocellulose and ensuring its uniform distribution in the glue. Epoxy resin and nanocellulose form a denser cross-linking structure through a cross-linking reaction, significantly improving the mechanical strength and heat resistance of the glue, while enhancing its barrier properties to prevent the penetration of water molecules and other harmful substances.

[0027] 3. The present invention can significantly improve the surface smoothness of the nylon layer by coating the PE wax on the surface, reduce friction and wear, and improve production efficiency. At the same time, the PE wax coating can effectively prevent the nylon layer from sticking during winding or stacking, ensuring smooth stratification of the composite film. In addition, the protective film formed by the PE wax can reduce scratches and damage on the surface of the nylon layer, maintain its integrity and aesthetics, and by adjusting the coating amount and concentration of the PE wax, the interface performance between the nylon layer and the composite glue can be optimized, the bonding strength between the layers of the composite film can be enhanced, and the stability and reliability of the overall performance can be ensured.

[0028] 4. The present invention provides a detailed preparation method, which includes coating a passivation liquid on the surface of an aluminum foil, compounding a nylon layer, an aluminum foil layer and a polypropylene cast film layer with a composite glue, performing a aging treatment, coating the surfaces of the nylon layer and the polypropylene cast film layer with PE wax and a lubricating powder, and finally performing molding and curing. The high quality and high reliability of the composite film are ensured by strict temperature and time control. DETAILED DESCRIPTION

[0029] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0030] Embodiment 1:

[0031] S1. Prepare the following raw materials: 75 parts of polycarbonate diol, 6 parts of polybutadiene-acrylonitrile copolymer diol, 3 parts of epoxy resin, 10 parts of tributyl citrate, and 8 parts of nanocellulose;

[0032] S2, stirring polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, and then adding epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenizing in a homogenizer at 5000 rpm for 20 min to obtain a composite glue;

[0033] S3. Prepare a passivation solution according to the following raw materials in parts by mass: 25 parts of acrylic resin, 8 parts of chromic acid, 1 part of vinyltrimethoxysilane, 2 parts of zinc phosphate, 0.3 parts of sodium polyacrylate, and 65 parts of deionized water.

[0034] S4, coating the passivation liquid on the surface of the aluminum foil, and then compounding the nylon layer, the aluminum foil layer and the polypropylene cast film layer with composite glue;

[0035] S5, then performing a aging treatment at 80° C. for 4 days;

[0036] S6. After aging and cooling, the surface of the nylon layer is coated with PE wax, and the surface of the polypropylene cast film layer is coated with lubricating powder. Finally, the film is molded and cured at a temperature of 35° C. and a relative humidity of 68%.

[0037] Embodiment 2:

[0038] S1. Prepare the following raw materials: 70 parts of polycarbonate diol, 5 parts of polybutadiene-acrylonitrile copolymer diol, 1 part of epoxy resin, 5 parts of tributyl citrate, and 5 parts of nanocellulose;

[0039] S2, stirring polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, and then adding epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenizing in a homogenizer at 5000 rpm for 20 min to obtain a composite glue;

[0040] S3. Prepare a passivation solution according to the following raw materials in parts by mass: 20 parts of acrylic resin, 5 parts of chromic acid, 0.5 parts of vinyltrimethoxysilane, 1 part of zinc phosphate, 0.1 parts of sodium polyacrylate, and 60 parts of deionized water.

[0041] S4, coating the passivation liquid on the surface of the aluminum foil, and then compounding the nylon layer, the aluminum foil layer and the polypropylene cast film layer with composite glue;

[0042] S5, then performing a aging treatment at 80° C. for 4 days;

[0043] S6. After aging and cooling, the surface of the nylon layer is coated with PE wax, and the surface of the polypropylene cast film layer is coated with lubricating powder. Finally, the film is molded and cured at a temperature of 35° C. and a relative humidity of 68%.

[0044] Embodiment 3:

[0045] S1. Prepare the following raw materials: 85 parts of polycarbonate diol, 7 parts of polybutadiene-acrylonitrile copolymer diol, 5 parts of epoxy resin, 15 parts of tributyl citrate, and 10 parts of nanocellulose;

[0046] S2, stirring polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, and then adding epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenizing in a homogenizer at 5000 rpm for 20 min to obtain a composite glue;

[0047] S3. Prepare a passivation solution according to the following raw materials in parts by mass: 30 parts of acrylic resin, 10 parts of chromic acid, 2 parts of vinyltrimethoxysilane, 3 parts of zinc phosphate, 0.5 parts of sodium polyacrylate, and 70 parts of deionized water.

[0048] S4, coating the passivation liquid on the surface of the aluminum foil, and then compounding the nylon layer, the aluminum foil layer and the polypropylene cast film layer with composite glue;

[0049] S5, then performing a aging treatment at 80° C. for 4 days;

[0050] S6. After aging and cooling, the surface of the nylon layer is coated with PE wax, and the surface of the polypropylene cast film layer is coated with lubricating powder. Finally, the film is molded and cured at a temperature of 35° C. and a relative humidity of 68%.

[0051] Embodiment 4:

[0052] The only difference from Example 1 is that the surface of the dragon layer is not coated with PE wax.

[0053] Embodiment 5:

[0054] The only difference from Example 1 is that the surface of the polypropylene cast film layer is not coated with lubricating powder.

[0055] Embodiment 6:

[0056] The only difference from Example 1 is that the aging treatment in step S5 is not performed.

[0057] Comparative Example 1:

[0058] The only difference from Example 1 is that the raw material in step S1 does not contain epoxy resin.

[0059] Comparative Example 2:

[0060] The only difference from Example 1 is that the raw material in step S1 does not contain tributyl citrate.

[0061] Comparative Example 3:

[0062] The only difference from Example 1 is that the raw material in step S1 does not contain nanocellulose.

[0063] Table 1: Performance test results of the multilayer composite films prepared in Examples 1-6 and Comparative Examples 1-3 after molding in a 50°C / 80%RH environment

[0064]

[0065] In summary, the present invention provides a detailed preparation method, including coating a passivation liquid on the surface of an aluminum foil, compounding a nylon layer, an aluminum foil layer and a polypropylene cast film layer with a composite glue, performing an aging treatment, and coating the surfaces of the nylon layer and the polypropylene cast film layer with PE wax and a lubricating powder, and finally performing molding and curing, and ensuring high quality and high reliability of the composite film through strict temperature and time control.

[0066] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0067] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0068] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A multilayer composite film for a battery cell, characterized in that: The multilayer composite film includes, from top to bottom, a nylon layer, an aluminum foil layer and a polypropylene cast film layer, and the nylon layer, the aluminum foil layer and the polypropylene cast film layer are bonded with a composite glue, wherein the composite glue includes the following raw materials in parts by weight: 70-85 parts of aromatic polyester polyol, 5-7 parts of oligomer polyol, 1-5 parts of epoxy resin, 5-15 parts of tributyl citrate, and 5-10 parts of nanocellulose.

2. A multilayer composite film for a battery cell according to claim 1, characterized in that: The aromatic polyester polyol is a polycarbonate diol.

3. The multilayer composite film for a battery cell according to claim 1, characterized in that: The oligomer polyol includes at least one of butadiene diol, polybutadiene-acrylonitrile copolymer diol and castor oil.

4. The multilayer composite film for a battery cell according to claim 1, characterized in that: The surface of the nylon layer is coated with PE wax.

5. A multilayer composite film for a battery cell according to claim 4, characterized in that: The concentration of PE wax coating is 1-3wt%, and the amount of dry glue coating is 0.1-0.

5.

6. The multilayer composite film for a battery cell according to claim 1, characterized in that: The surface of the aluminum foil layer is coated with a passivation solution, which includes the following raw materials in parts by weight: 20-30 parts of acrylic resin, 5-10 parts of chromium-containing compounds, 0.5-2 parts of silane coupling agents, 1-3 parts of phosphates, 0.1-0.5 parts of sodium polyacrylate, and 60-70 parts of deionized water.

7. The multilayer composite film for a battery cell according to claim 1, characterized in that: The surface of the polypropylene cast film layer is coated with lubricating powder.

8. A method for preparing a multilayer composite film for a battery cell as claimed in claim 1, characterized in that: The method comprises the following steps: S1. Apply a passivation solution on the surface of the aluminum foil, and then use a composite glue to composite the nylon layer, the aluminum foil layer and the polypropylene cast film layer; S2, then carry out aging treatment; S3. After aging and cooling, the surface of the nylon layer is coated with PE wax, and the surface of the polypropylene cast film layer is coated with lubricating powder, and finally the molding and curing are performed.

9. The method for preparing a multilayer composite film for a battery cell according to claim 8, characterized in that: The aging treatment temperature in step S2 is 70-85°C and the time is 3-5 days.

10. The method for preparing a multilayer composite film for a battery cell according to claim 8, characterized in that: The molding and curing temperature is 30-40°C and the relative humidity is 65-75%.

Citation Information

Patent Citations

  • Aluminum-plastic composite packaging film and preparation method thereof

    CN110497664A

  • Adhesive for electricity storage element packaging material, electricity storage element packaging material, container for electricity storage element, and electricity storage element

    CN116891715A

  • Reactive adhesive, laminate film, and package

    JP2020094154A